PENERAPAN STRATEGI KEHUMASAN DI UNIVERSITAS LANCANG KUNING - Junaidi, Junaidi (Universitas Lancang Kuning, 2009)
Public relationwn has an important role in creating an imige of an intitution. In conducting its responsibility, public relation needs to apply certain strategy in order public will pay attention to that intitution.